Bacteriocinogenic Enterococcus casseliflavus Isolated from Fresh Guava Fruit (Psidium guajava): Characterization of Bacteriocin ST192Gu and Some Aspects of Its Mode of Action on Listeria spp. and Enterococcus spp. - Svetoslav Dimitrov Todorov; Wilhelm Heinrich Holzapfel; John Robert Tagg (Fermentation, 2023)
Strain ST182Gu, isolated from fresh guava fruit, was identified as Enterococcus casseliflavus on the basis of biochemical tests, sugar fermentation reactions (API20Strip), PCR with genus-specific primers, and 16S rRNA sequencing. This appears to be the first documentation of the presence of this species in guava. E. casseliflavus ST182Gu was shown to produce a 4.8 kDa class IIa bacteriocin, active against various lactic acid bacteria including Enterococcus spp. and Streptococcus spp., and Staphylococcus aureus, and different serotypes of Listeria spp. The activity of the peptide was reduced by treatment with 0.1 mg/mL proteolytic enzymes, but not by α-amylase, catalase, lipase, and 1% (w/v) sodium dodecyl sulphate (SDS), Tween-20, Tween-80, urea, NaCl, and EDTA. No change in activity was recorded after adjustment to pH values of between 2.0 and 12.0 for 2 h, and after treatment at 100 °C for 120 min or 121°C for 20 min, compared with non-treated antimicrobial peptide. The mode of action against representative susceptible bacteria was shown to be bactericidal and associated with cell lysis and enzyme- and DNA-leakage. These susceptible bacteria, Listeria ivanovii subsp. ivanovii ATCC 19119, Listeria monocytogenes ATCC 15313, and Enterococcus faecalis ATCC 19443 differed however in their sensitivity to bacteriocin ST182Gu (6,553,600 AU/mL, 102,400 AU/mL, and 51,200 AU/mL, respectively). No significant differences were detected in cell growth and bacteriocin production when strain ST182Gu was grown in MRS broth at 26 °C, 30 °C, and 37 °C for 24 h. Bacteriocin ST182Gu recovery from the surface of the producer cells showed different activity, dependent of the applied test organisms (3200, 800 and 400 AU/mL, evaluated versus L. ivanovii subsp. ivanovii ATCC 19119, L. monocytogenes ATCC 15313 and E. faecalis ATCC 19443, respectively), however, with proportional values with the activity recorded in cell free supernatant versus same test microorganisms. When bacteriocin ST182Gu was combined with sublethal doses of ciprofloxacin, synergistic inhibition of L. ivanovii subsp. ivanovii ATCC 19119 was demonstrated. This increase in ciprofloxacin sensitivity may be due to the dissipation of the proton gradient in the cell membrane of the target organism associated with exposure to bacteriocin ST182Gu. Apart from reducing the MIC of classical therapeutic antibiotics, bacteriocins such as ST182Gu may also play an important role in the treatment of multidrug resistant strains.